An Apolipoprotein E Variant may Protect against Age-Related Macular Degeneration through Cytokine Regulation - Bojanowski, Christine M. (2006)
Age-related macular degeneration (AMD) is the leading cause of visual impairment and blindness among the elderly in Western countries. Genetic factors, age, cigarette smoking, nutrition, and exposure to light have been identified as AMD risk factors. In this study, we investigated the association between ApoE C112R/R158C single nucleotide polymorphisms (which determine the E2, E3, and E4 isoforms) and age-related macular degeneration (AMD), and the mechanism underlying the association. Genomic DNA was extracted from 133 clinically screened controls, 94 volunteers with a younger mean age, 120 patients with advanced AMD, and 40 archived ocular AMD slides for single nucleotide polymorphism typing. The effects of recombinant ApoE isoforms on CCL2 (a chemokine), CX3CR1 (a chemokine receptor), and VEGF (a cytokine) expression in cultured human retinal pigment epithelium (RPE) cells were tested and serum cholesterol profiles of the clinically screened subjects were analyzed. ApoE112R (E4) distribution differed significantly between AMD patients and controls. ApoE112R allele frequency was 10.9% in the AMD group when compared with 16.5% in the younger controls and 18.8% in the clinically screened controls. The pathologically diagnosed archived AMD cases had the lowest allele frequency of 5%. No significant differences in ApoE158C (E2) distribution were observed among the groups. A meta-analysis of 8 cohorts including 4,289 subjects showed a strong association between AMD and 112R, but not 158C. In vitro studies found that recombinant ApoE suppresses CCL2 and VEGF expression in RPE cells. However, the E4 isoform showed more suppression than E3 in both cases. These results further confirm the association between ApoE112R and a decreased risk of AMD development. The underlying mechanisms may involve differential regulation of both CCL2 and VEGF by the ApoE isoforms.